Взаємопов’язаний характер функцій мистецької освіти - Кучай Олександр; Kuchai Oleksandr; Kucsáj Olekszandr; Кучай Тетяна; Kuchai Tatiana; Kucsáj Tetjána; Чичук Антоніна; Chychuk Antonina; Csicsuk Antonina (Видавництво «Код», 2024)
Резюме. У статті виокремлено основні функції мистецької освіти та проаналізовано їх змістове наповнення. Зазначено, що жодна із функцій мистецької освіти не працює сама по собі, мистецька освіта – явище принципово поліфункціональне й чинить комплексний вплив на становлення духовності особистості у взаємозв’язку й взаємодоповнюваності. Тому ніколи не можна бути впевненим у перевазі однієї функції – поруч із виховною свої завдання вирішують і інші проаналізовані функції.

Abstract. The article highlights the main functions of art education and analyzes their content. It is noted that none of the functions of art education works by itself, art education is a phenomenon that is fundamentally multifunctional and has a complex impact on the development of the individual’s spirituality in connection and mutual complementarity. Therefore, one can never be sure of the superiority of one function – next to the educational one, other analyzed functions also solve their tasks. Art education has the most powerful means of influencing the process of spiritual formation of the personality – the emotional power of artistic and figurative understanding of reality. By awakening and deepening human feelings, art prompts thought to work, forms moral principles, expands the worldview, gives rise to ideals and, ultimately, not only enriches the sensual sphere of a person, but also significantly expands the horizons of his consciousness, directly influencing the formation of the spirituality of an individual. It has been proven that, on the one hand, the development of emotional intelligence significantly optimizes the development (deepening, diversification) of artistic cognition, which is based on emotion and its understanding. And on the other hand, the artistic knowledge of a person, based on his emotional and sensory sphere, focusing on emotional intelligence, at the same time develops it. In this way, artistic cognition gives impetus to a person’s understanding of a work of art and his own artistic activity as an artistic value, and at the same time allows him to live, understand, and appropriate life values laid down and individually figuratively interpreted in each work by its author. Therefore, the development of the emotional intelligence of an individual appears as a kind of methodological guideline for building a general strategy of art education, as it is an integral mechanism for the formation of personal values as a result of artistic knowledge. Therefore, it is clear that art is an integral part of the life of all people and society. And it doesn’t matter what kind of art a person likes or not. Against our will or at will, art will certainly influence our worldview and attitude to life.
The interrelated character of the functions of art education
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00014095 Редакційна колегія:https://sites.google.com/uica.education/nayka/%D1%80%D0%B5%D0%B4%D0%B0%D0%BA%D1%86%D1%96%D0%B9%D0%BD%D0%B0-%D0%BA%D0%BE%D0%BB%D0%B5%D0%B3%D1%96%D1%8F?authuser=0 Зміст:https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-8
Keywords: функції мистецької освіти; розвиток особистості; образотворче мистецтво; музика; хореографія; дизайн; підготовка студентів у галузі мистецької освіти